(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The study is prepared to determine the role of the most influential economic factor in the sales of the company’s shares and to measure the effect of the degree of diversification of insurance risks on the market value of the shares of the financial company. The importance of these sales in the market value of shares, and the study sample is from the Iraqi Dar Al-Salam Insurance Company for the period (2011-2020), and this research relied on the descriptive analytical approach, using the test of the hypothesis of dependence on statistical analysis, the coefficient of difference and the arithmetic mean, and the study concluded on the function The main objective of the investment portfolio is to reduce risks through diversification of the types of insurance. Thus, the insurance portfolio was able to reduce risks at a certain level of returns through the degree of correlation of the returns of the components of this portfolio.